THE INFLUENCE OF INTERNAL AUDIT FUNCTION ON PROMOTING EFFECTIVE CORPORATE GOVERNANCE BY USING THE MANAGEMENT SUPPORT IN COMMERCIAL IRAQI BANKS - Riyadh, Hosam Alden (The International Journal of Accounting and Business Society, 2017)
Good governance became a highly topical business issue at the beginning of the 21st century following a series of large corporate scandals and failures. This paper aims to set the conceptual framework for assessed the effects of internal audit function (IAF) on good governance in the public sector in Iraq. The objective of this paper to evaluate the internal audit function in promoting effective corporate governance among commercial banks in Iraq, While the specific objectives are to analyze the impact of work experience, the positioning, level of independence and the risk identification, measurement and prioritization approach by using management support adopted to internal audit function of commercial banks in Iraq. This paper will try to given that insights to develop the internal audit function in commercial organizations which is an important part of corporate governance reporting since it in a straight line affects the interests of all stakeholders such as customers, suppliers, employees, customers, creditors and government agencies as well highlighting to the need of change in outlook of theÂ  organizations team towards the internal audit function bearing in mind the importance of strong internal audit function for the growth of commercial banks which are valuable for the development of Iraq economy